Reproductive Health in Health Polices of Punjab Province: Gaps and Challenges - Madiha Nadeem; Ra'ana Malik (National University of Modern Languages (NUML), Islamabad, 2023)
Pakistan has to place a strong emphasis on reproduction as part of an inclusive healthcare strategy that would improve the general health of its population. The aim of this paper is to analyze the health policies of the Punjab Province post-18th Amendment by focusing on the area of reproductive health. For this purpose, health policies were analyzed thematically. After reviewing and analyzing policies, we identified areas of concern about reproductive health care, including the lack of infrastructure and human resources and the lack of evidence-based health-related data and research to respond to or design need-based initiatives. Additionally, reproductive health seems to revolve around special issues and target communities by taking international commitments to the Millennium Development Goals and Sustainable Development Goals as a guideline (maternal and child health and prevention of sexually transmitted diseases). It is also found that significant donor funds are only related to family planning and maternal and child care services. These findings indicate that reproductive health measures regulate the fertility and sexual behavior of the target community, along with focusing more on maternal health, which somehow reveals the prevailing gender norms regarding roles in society. Reproductive health issues among men, transgender people, and non-parents are ignored. It is hoped that the identified gaps might be helpful in planning and ensuring access, quality, and equity in reproductive health services.